Benzobisthiadiazole-based high-spin donor–acceptor conjugated polymers with localized spin distribution. Issue 9 (29th March 2021) - Sabuj, Md Abdus; Huda, Md Masrul; Sarap, Chandra Shekar; Rai, Neeraj
Abstract : This work indicates that carefully selected acceptor units can lead to a localized spin topology and a high-spin ( S = 1) ground-state with a pure diradical ( y 0 = 1) character suitable for organic magnetic materials. Abstract : Stable organic semiconductors (OSCs) with a high-spin ground-state can profoundly impact emerging technologies such as organic magnetism, spintronics, and medical imaging. Over the last decade, there has been a significant effort to design π-conjugated materials with unpaired spin centers. Here, we report new donor–acceptor (D–A) conjugated polymers comprising cyclopentadithiophene and cyclopentadiselenophene donors with benzobisthiadiazole (BBT) and iso-BBT acceptors. Density functional theory calculations show that the BBT-based polymers display a decreasing singlet–triplet energy gap with increasing oligomer chain length, with degenerate singlet and triplet states for a N = 8 repeat unit. Furthermore, a considerable distance between the unpaired electrons with a pure diradical character disrupts the π-bond covalency and localizes the unpaired spins at the polymer ends. However, replacing the BBT acceptor with iso-BBT leads to a closed-shell configuration with a low-spin ground-state and a localized spin density on the polymer cores. This study shows the significance of the judicious choice of π-conjugated scaffolds in generating low- ( S = 0) and high-spin ( S = 1) ground-states in the neutral form, by modulation of spin topology in extended π-conjugated D–A polymers for emergent optoelectronic applications.